Aglaotilla, a new genus of Australian Mutillidae (Hymenoptera) with metallic coloration - Brothers, Denis J. (Zootaxa, 2018)
The genus Aglaotilla Brothers, gen. nov., is described for 14 striking species of Australian Mutillidae related to Ephutomorpha André, 1902, characterized by bright metallic coloration and strong punctation. The description of both sexes is possible through sex associations revealed by rearings from mud nests and trap nests. Both sexes of the type species, Ephutomorpha submetallescens Turner, 1916, are described and illustrated, the male for the first time. New combinations and a new name are proposed, as follows: Aglaotilla aeruginosa (Smith, 1879), comb. nov. (from Mutilla); A. australis (André, 1898), comb. nov. (from Mutilla); A. cuprea (André, 1901), comb. nov., stat. nov. (from Mutilla); A. dilecta (Turner, 1916), comb. nov. (from Ephutomorpha); A. ignita (Smith, 1855), comb. nov. (from Mutilla); A. metallica (Smith, 1855), comb. nov. (from Mutilla); A. mira (André, 1895), comb. nov. (from Mutilla (Sphaerophthalma [sic.])); A. nigroaenea (Smith, 1855), comb. nov. (from Mutilla); A. picturata (Turner, 1914), comb. nov. (from Ephutomorpha); A. semicuprea (André, 1898), comb. nov. (from Mutilla); A. submetallescens (Turner, 1916), comb. nov. (from Ephutomorpha); A. viridatis (Smith, 1855), comb. nov. (from Mutilla); A. viridiaurea (André, 1895), comb. nov. (from Mutilla (Sphaerophthalma [sic.])); A. discolor Brothers, nom. nov. (= Ephutomorpha aeneidorsis Turner, 1916, not Ephutomorpha lauta var. aeneidorsis André, 1903).